ASSOCIATION OF COGNITIVE DYSFUNCTION AND ANAEMIA EMPLOYING TMT-BAND DSST TESTS - MOHIT TRIVEDI; R. K. DIXIT (International Journal of Pharma and Bio Sciences, 2013)
Anemia is one of the commonest conditions worldwide and it is known to produce cognitive deficits in children adolescents and adults. Now compelling evidence is emerging about the detrimental effect of anaemia on the cognitive functions of the brain. 30 patients with anaemia were matched against 30 controls . The tools used were TMT-B and DSST. Data were presented as mean and analyzed using students t test , and chi square test.RESULTS: Anaemics performed poorly in TMT-B and DSST and made more number of errors in both the tests which was very highly significant. CONCLUSION: Anaemic patients had significant circumscribed areas of cognitive dysfunctions compared to the control group but a clear relation between the severity of anaemia and the severity of cognitive dysfunction could not be established .